EKSKLUSIVISME BAHAUDDIN NURSALIM: Radikalisasi dan Ideologisasi Ayat Interagama di Youtube - Fikri Fanani; Fanani, Fikri; Harianto, Agus (Wahana Islamika: Jurnal Studi Keislaman, 2022)
According to Komaruddin Hidayat, there are 5 types of mapping of religious attitudes typology: exclusivism, inclusivism, pluralism, eclecticism, and universalism. These five typologies have an impact on religious life in Indonesia. For Moqsith Ghazali, the typology of exclusivism is not suitable for living a pluralistic life, such as in Indonesia with six recognized religions. Exclusivism is an understanding that puts forward the truth of the religion it adheres to and blames other religions. The writer finds this exclusive way of thinking in the thoughts of Gus Baha, the ulema who all circles have recently accepted. Through his research on Youtube, the author found five videos that represent his exclusivism. How can exclusivism be accepted in a society that should not be suitable for living in the midst of a pluralistic religious life. Moreover, Indonesia frees its people to follow any religion they believe in without judging which religion is right and which one is wrong. By means of inductive thinking, the author has tracked down several videos of Gus Baha and selected 5 videos that will be used as the primary source of this research. As for theoretically, the author uses the theory of language criticism popularized by Roger Flower and his friends.